2010
DOI: 10.1177/0961203310383301
|View full text |Cite
|
Sign up to set email alerts
|

Elevation of serum CXCL13 in SLE as well as in sepsis

Abstract: Recent studies have demonstrated that CXCL13 serum levels correlate significantly with systemic lupus erythematosus (SLE) disease activity. However, experimental studies show that CXCL13 production can also be induced by bacterial exposure as well as in response to inflammatory cytokines. This report asks whether CXCL13 serum levels are elevated in patients with evidence of bacterial infections and whether there is a correlation with the C-reactive protein (CRP) levels or the severity of illness in critically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 17 publications
4
20
0
Order By: Relevance
“…In this context, serum samples of septic patients were analysed. It was found that serum CXCL13 levels in septic patients were comparably high, as in patients with active SLE [39]. Therefore, CXCL13 serum levels cannot be used to distinguish between an active autoimmune response and severe infectious diseases.…”
Section: Cxcl13 and Sle: From Bench To Bedsidementioning
confidence: 99%
See 1 more Smart Citation
“…In this context, serum samples of septic patients were analysed. It was found that serum CXCL13 levels in septic patients were comparably high, as in patients with active SLE [39]. Therefore, CXCL13 serum levels cannot be used to distinguish between an active autoimmune response and severe infectious diseases.…”
Section: Cxcl13 and Sle: From Bench To Bedsidementioning
confidence: 99%
“…In one study on 91 Caucasian patients, CXCL13 serum levels were correlated with disease activity using the SLE Disease Activity Index (SLEDAI) and to lupus nephritis. It was found that serum CXCL13 levels correlated well with SLEDAI and median CXCL13 concentrations were higher in patients with renal involvement [39]. In a further study on 35 Asian patients with SLE, plasma concentrations of CXCL13 were assessed.…”
Section: Cxcl13 and Sle: From Bench To Bedsidementioning
confidence: 99%
“…In the search for a clinical marker facilitating early diagnosis of PTLD we examined CXCL13 serum‐levels in pediatric patients with PTLD and EBV reactivation, as well as in healthy controls. In a previous study we demonstrated, that serum CXCL13 levels can be considered stable in serum and therefore is easily applicable for clinical use (15).…”
Section: Discussionmentioning
confidence: 99%
“…Soluble biomarkers include the triggering receptor expressed on myeloid cells-1 (sTREM-1) and pentraxin 3 (PTX3) [38], phagocyte-specific S100A8/A9 protein levels [12] and CXC ligand 13 protein (CXCL13) serum levels [39]. These tests have the advantage of being tested by enzymelinked immunosorbent assay (ELISA), which makes them cheaper and faster to detect than analyses performed by flow cytometry or real-time PCR.…”
Section: New Markersmentioning
confidence: 99%
“…However, experimental studies show that CXCL13 production can also be induced by bacterial exposure as well as in response to inflammatory cytokines [52]. Nevertheless, Shiffer at al [39] showed that CXCL13 levels were increased in SLE patients with evidence of a bacterial infection as well as in patients with active SLE.…”
Section: Ligand 13 Proteinmentioning
confidence: 99%